Oral Microbiome and Gingival Tissue Apoptosis and Autophagy Transcriptomics - Ebersole, Jeffrey L.; Kirakodu, Sreenatha S.; Neumann, Elliot; Orraca, Luis; Gonzalez Martinez, Janis; Gonzalez, Octavio A. (Frontiers in Immunology, 2020)
Apoptosis and autophagy are described as important regulators of cellular functions, particularly related to nutritional stress that could be induced by infection and inflammation. As such, recent results support an important role for each of these cell death or survival pathways in regulating inflammatory and immune responses. Periodontitis represents a complex chronic microbial challenge by a dysbiotic microbiome that results in a persistent inflammatory response and a tissue destructive immunoinflammatory lesion. Although there are clear clinical symptoms of this disease including soft and hard tissue destruction of the periodontium, the underlying biology of the host-bacterial interactions that lead to initiation, progression, and resolution of the disease remain less clear. We have used a nonhuman primate model of ligature-induced experimental periodontal disease to try to model these host-bacterial interactions. Objective: This study focused on documenting characteristics of the gingival transcriptome during various stages of periodontitis targeting genes associated with apoptotic and autophagic pathways and changes that specifically associate with features of the oral microbiome. Methods: Macaca mulatta (n=18; 12-23 years) were examined at baseline and 0.5, 1, and 3 months of disease progression, as well as 5 months with clinical disease resolution. 16S sequencing and microarray analyses examined changes in the microbiome and gingival transcriptome respectively at each time point from every animal. Results: Specific patterns of apoptotic and autophagic genes were identified related to the initiation and progression of disease. The analysis also provided insights on the principal bacteria within the complex microbiome whose abundance was significantly correlated with differences in apoptotic and autophagic gene expression. Bacteria were identified that formed associated complexes with similar effects on the host gene expression profiles. A complex of Leptotrichia_unclassifed, Capnocytophaga_unclassified, Prevotella sp. 317, and Veillonellaceae_[G-1] sp. 155 were significantly negatively correlated with both apoptosis and autophagy. Whereas, Veillonellaceae_[G-1], Porphyromonadaceae, and F. alocis 539 were significantly positively correlated with both pathways, albeit this relationship was primarily associated with pro-apoptotic genes. Conclusions: The findings provide evidence for specific bacteria/bacterial complexes within the oral microbiome that appear to have a more substantive effect on regulating apoptotic and autophagic pathways in the gingival tissues with periodontitis.